2023
DOI: 10.3847/2041-8213/acda2f
|View full text |Cite
|
Sign up to set email alerts
|

A Candidate Dual QSO at Cosmic Noon

Abstract: We report the discovery of a candidate dual QSO at z = 1.889, a redshift that is in the era known as “cosmic noon” where most of the universe’s black hole and stellar mass growth occurred. The source was identified in Hubble Space Telescope WFC3/IR images of a dust-reddened QSO that showed two closely separated point sources at a projected distance of 0.″26, or 2.2 kpc. This red QSO was targeted for imaging to explore whether red QSOs are hosted by merging galaxies. We subsequently obtained a spatially resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Comprehensive multiwavelength follow-up observations are usually required to distinguish one from the others (e.g., Liu et al 2019;Chen et al 2023b;Gross et al 2023b). Despite the continued observational effort of finding promising candidate kiloparsecscale dual AGNs at z > 1 (e.g., Yue et al 2021;Glikman et al 2023), only a few systems with separations below 5 kpc are robustly confirmed (Junkkarinen et al 2001;Mannucci et al 2022;Chen et al 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive multiwavelength follow-up observations are usually required to distinguish one from the others (e.g., Liu et al 2019;Chen et al 2023b;Gross et al 2023b). Despite the continued observational effort of finding promising candidate kiloparsecscale dual AGNs at z > 1 (e.g., Yue et al 2021;Glikman et al 2023), only a few systems with separations below 5 kpc are robustly confirmed (Junkkarinen et al 2001;Mannucci et al 2022;Chen et al 2023b).…”
Section: Introductionmentioning
confidence: 99%